Retirement Security in an Aging Population - Poterba, James M. (American Economic Review, 2014)
Elderly individuals exhibit wide disparities in their sources of income. For those in the bottom half of the income distribution, Social Security is the most important source of support; program changes would directly affect their well-being. Income from private pensions, assets, and earnings are relatively more important for higher-income elderly individuals, who have more diverse income sources. The trend from private sector defined benefit to defined contribution pension plans has shifted responsibility for retirement security to individuals. A significant subset of the population is unlikely to be able to sustain their standard of living in retirement without higher pre-retirement saving.